Impact of Internal Control on Fraudulent Financial Statement Of State Owned Enterprises - Muhammad Jawad Zaki; Zaldy Adrianto (International Journal of Management and Business Economics, 2026)
This study examines the influence of internal control effectiveness on the likelihood of financial statement fraud among 26 State-Owned Enterprises (SOEs) during the 2023–2024 period, using secondary data obtained from annual reports and analyzed through a Common Effect Model regression. Internal control effectiveness is measured using an Internal Control Index, while the probability of fraudulent reporting is proxied by the Beneish M-Score. The findings reveal that internal controls, in aggregate, have a significant negative effect on the potential for financial statement fraud. At the component level, Risk Assessment, Information and Communication, and Monitoring show significant negative effects, whereas Control Environment and Control Activities do not exhibit significant influence. Moreover, the average Beneish M-Score indicates a tendency toward potential financial reporting fraud within the sampled SOEs.